The Factors Influencing Teaching (FIT)-Choice scale in a Dutch teacher education program - Fokkens-Bruinsma, Marjon; Canrinus, Esther T. (Asia-Pacific journal of teacher education, 2012)
This study examined the suitability of the FIT-Choice scale in a Dutch educational context among two cohorts of preservice teachers (Ns = 62, 89), surveyed at the end and the beginning of their one-year program respectively. The relationships between the motivations for becoming a teacher and concurrent commitment were examined, as well as the differences between the two cohorts. The factor analyses were consistent with the original FIT-Choice structure. The main motivation for becoming a teacher was the self-perception of teaching-related ability. Affective commitment was predicted by the motivations of teaching ability, working with children, prior teaching and learning experiences, and time for family, as well as satisfaction with the choice of teaching and perceived task demand. Lastly, preservice teachers at the end of their teacher education considered social influences and teaching ability to be more important motivations for becoming a teacher.